F19 Exploring the issue of swallowing in huntington's disease. (16th November 2010) - Ho, A K; Drake, K; Cull, J; Barker, R A; Tabrizi, S J; Lee, P
Abstract : Background: While swallowing function is known to be affected in the later stages of Huntington's disease, far less is known in the earlier stages of disease. Aims: This study investigated swallowing and the impact of changes in swallowing issues in patients at different stages of Huntington's disease severity. Methods: Thirty nine people with Huntington's disease completed the Swallowing Quality of Life questionnaire. These participants were at different disease stages, ranging from premanifest to the later stages of Huntington's disease. Results: We found that there was a significant difference between Stage 4 and Stage 5 patients where the latter group scored more poorly on all the following aspects of swallowing, that is symptom frequency, social function (as a results of swallowing difficulties), eating desire and eating duration. On the symptom frequency measure, Stage 3 participants showed a significantly poorer score compared to Stage 2 group, and the Stage 1 group also showed a significantly poorer score relative to the premanifest group. There was also a trend for Stage 1 participants to score more poorly for the eating duration score relative to the premanifest group. Conclusions: There was a general increase of swallowing-related symptoms particularly between Stages 4 to 5. Furthermore, there was some evidence of a gradual and earlier onset of involvement where swallowing related changes in participants begin to appear much earlier on.